Synergistic Integration of LQR Control and PSO Optimization for Advanced Active Suspension Systems Utilizing Electro-Hydraulic Actuators and Electro-Servo Valves - Trong Tu (EMITTER International Journal of Engineering Technology, 2025)
This paper investigates the design and optimization of Linear Quadratic Regulator (LQR) controllers for vehicle active suspension systems, incorporating an electro-hydraulic actuator with an electro-servo valve. To enhance both vehicle comfort and road-holding stability, we employ Particle Swarm Optimization (PSO) to optimize the LQR controller parameters. The active suspension system model includes the dynamics of the electro-hydraulic actuator and the electro-servo valve, providing a realistic and practical framework for heavy vehicles. By leveraging PSO, the LQR controller parameters are fine-tuned to minimize a cost function that integrates both comfort and stability up to 76.91%. The results demonstrate substantial improvements in ride comfort and road-holding stability compared to traditional passive suspension systems. This research remarks the fundamentals of the experimental validation and further refinement of these control algorithms to adapt to various driving conditions and vehicle models, ultimately aiming to transition these optimized controllers from theoretical frameworks to practical, real-world applications.